Avaliação da influência da atividade física aeróbia e anaeróbia na progressão do câncer de pulmão experimental - Cal, Rodrigo Nunes (2012)
Introduction: Lung cancer is one of the most incident neoplasms in the world representing the main cause of mortality for cancer. Many epidemiologic studies have suggested that physical activity may reduce the risk of lung cancer, other works evaluate the effectiveness of the use of the physical activity in the suppression, remission and reduction of the recurrence of tumors. Objective: To evaluate the effects of aerobic and anaerobic physical activity in the development and the progression of lung cancer. Material and Methods: Lung tumors were induced with a dose of 3mg of Urethane/kg, in 67 male Balb - C type mice, divided in three groups: Group 1 - 24 mice treated with Urethane and without physical activity; Group 2 - 25 mice with Urethane and subjected to aerobic swimming free exercise; Group 3 - 18 mice with urethane, subjected to anaerobic swimming exercise with gradual loading 5 to 20% of body weight. All the animals were sacrificed after 20 weeks, and lung lesions were analyzed. Results: The median number of lesions (nodules and hyperplasia) was 3.0 for group 1, 2.0 for group 2 and 1.5 to 3 (p = 0.052). When compared only the presence or absence of lesion, there was a decrease in the number of lesions in group 3 compared with group 1 (p = 0.03) but not in relation to group 2. There were no metastases or other changes in other organs. Conclusion: The anaerobic physical activity but not aerobical, diminish the incidence of experimental lung tumors.